Static axial overloading primes lumbar caprine intervertebral discs for posterior herniation - Paul, Cornelis P. L. (PLoS One, 2017)
INTRODUCTION: Lumbar hernias occur mostly in the posterolateral region of IVDs and mechanical loading is an important risk factor. Studies show that dynamic and static overloading affect the nucleus and annulus of the IVD differently. We hypothesize there is also variance in the effect of overloading on the IVD’s anterior, lateral and posterior annulus, which could explain the predilection of herniations in the posterolateral region. We assessed the regional mechanical and cellular responses of lumbar caprine discs to dynamic and static overloading. MATERIAL AND METHODS: IVDs (n = 125) were cultured in a bioreactor and subjected to simulated-physiological loading (SPL), high dynamic (HD), or high static (HS) overloading. The effect of loading was determined in five disc regions: nucleus, inner-annulus and anterior, lateral and posterior outer-annulus. IVD height loss and external pressure transfer during loading were measured, cell viability was mapped and quantified, and matrix integrity was assessed. RESULTS: During culture, overloaded IVDs lost a significant amount of height, yet the distribution of axial pressure remained unchanged. HD loading caused cell death and disruption of matrix in all IVD regions, whereas HS loading particularly affected cell viability and matrix integrity in the posterior region of the outer annulus. CONCLUSION: Axial overloading is detrimental to the lumbar IVD. Static overloading affects the posterior annulus more strongly, while the nucleus is relatively spared. Hence, static overloading predisposes the disc for posterior herniation. These findings could have implications for working conditions, in particular of sedentary occupations, and the design of interventions aimed at prevention and treatment of early intervertebral disc degeneration.